STATE SOVEREIGNTY IN GEORGIAN POLITICAL THINKING AND PRACTICE - RTSKHILADZE, Gulbaat (CENTRAL ASIA AND THE CAUCASUS, 2007)
Along with the concepts of “state” and “territory,” sovereignty is one of the central themes both in the study and practice of international relations.1 The sovereignty issue is all-important for Georgia as a post-Soviet “transition state” still working on its statehood.State sovereignty and state independence are inextricably related to the nation-state2 as the main actor in the contemporary international system. (There is no doubt that Georgia is one such state.) Independence within a nation-state can be rationally substantiated as a political tool used to achieve and realize the highest values, as well as specific positive aims and tasks pursued by the population of any sovereign state taking due account of its economic, scientific, cultural, spiritual, etc. development, which cannot be affected by outside factors. Aristotle regarded state sovereignty as a tool in the context of his “happy state” conception; a sovereign state helped realize the highest values and achieve the ultimate aims of its population.3 On the other hand, Aristotle pointed out: “For a state is not a mere aggregate of persons, but a union of them sufficing for the purposes of life.”4 This is not a purely instrumental and axiological idea of statehood and sovereignty—the philosopher supplied their final axiological interpretation. Normally nation-states regard sovereignty as their highest value and ultimate aim.5 State and national independence develop into the ultimate value with no fair equivalent, even if overpriced.6 This is particularly typical of peoples with a mythologized national identity; they regard themselves as a living organism with a creative force and spiritual identity.7 For most so-called de-mythologized peoples that mostly regard themselves as a “society” rather than a “nation,”8 sovereignty is an indisputable value. The point has been amply demonstrated by international experience.9Inevitably, there are exceptions: for example, the Scots, a nation with a highly developed national self-identity, voluntarily abandoned their sovereignty and independence, while the Canadians, Australians, and some other people's formally delegated their sovereignty to the English crown. There is another type of collective self-identification that abandons national and state sovereignty in favor of other, much larger entities. It is rooted in a shared culture, faith, language, etc. I have in mind pan Slavism, pan-Turkism, pan-Islamism, and other similar phenomena,10 the success of which is always short-lived or even virtual.The above is part of my discussion, within the limits of the present article, of whether sovereignty as an ultimate aim is self-sufficient and valuable for Georgia at the level of the political elites and society as a whole; how important is sovereignty as a tool for realizing other important values and aims, i.e. what does the political class and society mean by sovereignty, and what specific features can be observed in this connection; how does the present idea of sovereignty in Georgia affect political practice (particularly the country’s foreign policy orientation and implementation of the republic’s strategic objectives)